Erect Penile Length and Circumference Dimensions of 1, 661 Sexually Active Men in the United States. (10th July 2013) - Herbenick, Debby; Reece, Michael; Schick, Vanessa; Sanders, Stephanie A.
Abstract Introduction Penile size continues to receive popular and empirical attention. Little is known about the process of self‐measurement and whether the behaviors a man engages in to become erect for self‐measurement are associated with his erect penile dimensions. Aims The article aims to assess men's erect penile dimensions in a study in which the men would presumably be motivated to report accurate information about their penis size; and to explore associations between men's erect penile dimensions, their method of measurement, and their demographics. Methods Data are from an Internet‐based baseline phase of a large prospective daily diary study that compared men's use of a standard‐sized condom to men's use of a condom sized to fit their erect penis. Main Outcome Measures The main outcomes are participant characteristics, activities engaged in during self‐measurement process, and self‐reported erect penile length and circumference. Results For this sample of 1, 661 men, the mean erect penile length was 14.15 cm (SD = 2.66; range = 4 to 26 cm), and the mean erect penile circumference was 12.23 cm (SD = 2.23; range = 3 to 19). Participant characteristics were not associated with measured length or circumference. Most men measured their penis while alone, using hand stimulation to become erect. Conclusions In this sample of men who measured their erect penile length and circumference for the purposes of receiving a condom sized to fit their erect penis, we found a mean erect penile length of 14.15 cm and a mean erect penile circumference of 12.23 cm. The self‐reported erect penile dimensions in this study are consistent with other penile dimension research. Also, findings suggest that mode of getting an erection may influence erect penile dimensions. Additionally, how a man becomes erect for self‐measurement may be associated with his erect penile length and/or circumference. Herbenick D, Reece M, Schick V, and Sanders SA. Erect penile length and circumference dimensions of 1, 661 sexually active men in the United States. J Sex Med 2014;11:93–101.